Cost-effectiveness of KRAS, EGFR and ALK testing for decision making in advanced nonsmall cell lung carcinoma: the French IFCT-PREDICT.amm study. Issue 3 (15th March 2018) - Loubière, Sandrine; Drezet, Alexandre; Beau-Faller, Michèle; Moro-Sibilot, Denis; Friard, Sylvie; Wislez, Marie; Blons, Hélène; Daniel, Catherine; Westeel, Virginie; Madroszyk, Anne; Léna, Hervé; Merle, Patrick; et al.
ALK rearrangement and EGFR / KRAS mutations constitute the primary biomarkers tested to provide targeted or nontargeted therapies in advanced nonsmall cell lung cancer (NSCLC) patients. Our objective was to assess the cost-effectiveness of biomarker testing for NSCLC. Between 2013 and 2014, 843 treatment-naive patients were prospectively recruited at 19 French hospitals into a longitudinal observational cohort study. Two testing strategies were compared, i.e. with "at least one biomarker status known" and "at least KRAS status known", in addition to "no biomarker testing" as the reference strategy. The Kaplan–Meier approach was employed to assess restricted mean survival time. Direct medical costs incurred by hospitals were estimated with regard to treatment, inpatient care and biomarker testing. Compared with "no biomarker testing", the "at least one biomarker status known" strategy yielded an incremental cost-effectiveness ratio of EUR13 230 per life-year saved, which decreased to EUR7444 per life-year saved with the "at least KRAS status known" testing strategy. In sensitivity analyses, biomarker testing strategies were less costly and more effective in 41% of iterations. In summary, molecular testing prior to treatment initiation proves to be cost-effective in advanced NSCLC management and may assist decision makers in defining conditions for further implementation of these innovations in general practice. KRAS, EGFR and ALK molecular testing before treatment initiation proves to be cost-effective in advanced NSCLC http://ow.ly/Ld1Z30ia9qv